Single photon detection and manipulation in photonic integrated circuits - Yanikgonul, Salih (Nanyang Technological University, 2021)
One way to achieve a scalable quantum computing and communication platform is to construct a network of quantum systems. Building a quantum network with photonic integrated circuits (PICs) is a promising avenue as they provide a platform on which quantum information can be generated and manipulated via integrated photonic structures. One such example would be a hybrid PIC with quantum light sources, modulators, interferometers, and single-photon detectors for complete on-chip single-photon processing.